The Effect of the Irradiation Geometry on the Image Quality Obtained by Gamma Transmission Method - Küçer, Nermin; Girgin, Ali (İstanbul Kültür Üniversitesi Yayınları, 2003)
The effect of the irradiation and counting geometry on the image quality obtained by gamma transmission method has been investigated. As the object for imaging, an absorber was made out using aluminium and lead plates with the dimensions of 40 mm., 20 mm., 4mm. framed with Plexiglas. The absorber has been irradiated with the 662 ke V gamma rays of Cs -137, which were collimated in different apertures. A 4.44 cm.x5.87 cm. Nal(Tl) crystal was used to detect the gamma rays transmitted through absorber. The beam intensity distributions were measured for different collimator and beam width. The measurements have been repeated for the different source-to-detector distances to accommodate the beam intensity.

Gamma transmisyon yöntemiyle elde edilen görüntü kalitesine ışınlanma ve sayım geometrisinin etkisi incelendi. Görüntülenecek obje olarak pleksiglas çerçeveli 40mm.x20 mm.z4mm. boyutlarında alüminyum ve kurşun levhalar kullanılarak bir soğurucu oluşturuldu. Soğurucu, farklı genişliklerde kolime edilmiş Cs-137’nin 662keV’lik gamma ışın demetleriyle ışınlandı. Soğurucudan geçen gamma ışınlarını saymak için 4.44 cm.x.5.87 cm.lik NaI(Tl) kristali kullanıldı. Farklı kolimatör ve demet genişliği için, demet-şiddet dağılımları ölçüldü. Demet şiddetini uygun hale getirmek için ölçümler, farklı kaynak-detektör uzaklıklarında tekrar edildi.
Keywords: irradiation geometry; image quality; gamma transmission method; ışınlama geometrisi; görüntü kalitesi; gama iletim yöntemi